Assessing genetic diversity of Mycobacterium tuberculosis by spoligotyping and IS6110-based restriction fragment length polymorphism in North India - Jitendra Prasad Mathuria; Pragya Sharma; Pradyot Prakash; Jai Kumar Samaria; Vishwa Mohan Katoch; Shampa Anupurba (International Journal of Mycobacteriology, 2016)
Objective/background: Molecular epidemiology methods are very useful for differentiating between strains, assessing their diversity, and measuring the prevalence of the most circulating strain in an area. Various molecular typing methods using different molecular markers have been utilized worldwide, such as restriction fragment length polymorphism (RFLP), spoligotyping, Mycobacterial Interspersed Repetitive Unit – Variable Number of Tandem Repeat (MIRU-VNTR), and Double repetitive element-PCR (DRE-PCR) typing, for simultaneous detection and epidemiologic typing of Mycobacterium tuberculosis. The present study is conducted to assess the genetic diversity of M. tuberculosis by IS6110-RFLP and spoligotyping in patients attending a tertiary care hospital in eastern Uttar Pradesh, North India. Methods: A total of 83 representative isolates of M. tuberculosis were included in this study. These isolates were subjected to spoligotyping and IS6110-RFLP DNA fingerprinting techniques as described previously. Results: The spoligotype patterns were compared with SpolDB4.0; patterns of 64 out of 83 M. tuberculosis isolates were matched with the available data, while 19 isolates were found to be orphan, that is, absent in the SpolDB4.0 database. The majority of the M. tuberculosis strains (56.5%) belong to central Asian (32.5%), ill defined T (13.2%), and Beijing (10.8%) families. On IS6110-RFLP analysis, in 19.2% (16/83) of these isolates, IS6110 element was not found (0 copy number strains). Further, 15.6% (13/83) isolates were found to be low-copy-number strains having less than six copies of IS6110 element, and the remaining 65.0% (54/83) were multiple-copy-number strains with six or more copies of the element. On comparing the results of spoligotyping and IS-6110-RFLP, a total of 47 isolates were clustered by spoligotyping; out of these isolates, 40 were found to be unique by IS6110-RFLP. Conclusion: Spoligotype analysis resulted in the grouping of a much larger number of isolates within apparently identical clusters compared with IS6110-RFLP typing, while IS6110-RFLP was not found to effectively distinguish between zero- and low-copy-number isolates. Therefore, we concluded that, in India, the use of both the techniques simultaneously for DNA fingerprinting of M. tuberculosis could be a better approach.